2023
DOI: 10.1002/open.202200266
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Saccharomyces cerevisiae for the de novo Production of Halogenated Tryptophan and Tryptamine Derivatives

Abstract: The indole scaffold is a recurring structure in multiple bioactive heterocycles and natural products. Substituted indoles like the amino acid tryptophan serve as a precursor for a wide range of natural products with pharmaceutical or agrochemical applications. Inspired by the versatility of these compounds, medicinal chemists have for decades exploited indole as a core structure in the drug discovery process. With the aim of tuning the properties of lead drug candidates, regioselective halogenation of the indo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…These results confirmed that in each case only a single chlorotryptophan was present in detectable amounts in the broth. This is in keeping with other recent work on halogenase expression in yeast. , Aside from some variability when coexpressing Eco Frb from Escherichia coli, the activity of these three FDHs did not vary significantly between reductases and Eco SsuE from E. coli was selected for further experiments.…”
Section: Resultsmentioning
confidence: 99%
“…These results confirmed that in each case only a single chlorotryptophan was present in detectable amounts in the broth. This is in keeping with other recent work on halogenase expression in yeast. , Aside from some variability when coexpressing Eco Frb from Escherichia coli, the activity of these three FDHs did not vary significantly between reductases and Eco SsuE from E. coli was selected for further experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Integration of S. cerevisiae ST7574 (CEN.PK113-7D) with SrPyrH , SttH , and LaRebH . The highest titers obtained for halogenated tryptophan and tryptamine were 3.56 ± 0.24 mg/L 7-bromotryptophan and 2.42 ± 0.31 mg/L 7-chlorotryptamine ( Milne et al, 2023 ).…”
Section: The Industrial Production Of L-trpmentioning
confidence: 99%